Resolution of inflammation during rheumatoid arthritis - Ye, Xiaoou; Ren, Dan; Chen, Qingyuan; Shen, Jiquan; Wang, Bo; Wu, Songquan; Zhang, Hongliang (Frontiers in Cell and Developmental Biology, 2025)
Rheumatoid arthritis (RA) is a chronic autoimmune disease that causes synovial joint inflammation as well as bone destruction and erosion, typically characterized by joint pain, swelling, and stiffness, with complications and persistent pain after remission posing a significant health burden for RA patients. The etiology of RA has not yet been fully elucidated, but a large number of studies have shown that the initiation of inflammation in RA is closely related to T-cell activation, the production of a variety of pro-inflammatory cytokines, macrophage M1/M2 imbalance, homeostatic imbalance of the intestinal flora, fibroblast-like synoviocytes (FLSs) and synovial tissue macrophages (STMs) in the synovial lumen of joints that exhibit an aggressive phenotype. While the resolution of RA is less discussed, therefore, we provided a systematic review of the relevant remission mechanisms including blocking T cell activation, regulating macrophage polarization status, modulating the signaling pathway of FLSs, modulating the subpopulation of STMs, and inhibiting the relevant inflammatory factors, as well as the probable causes of persistent arthritis pain after the remission of RA and its pain management methods. Achieving resolution in RA is crucial for improving the quality of life and long-term prognosis of patients. Thus, understanding these mechanisms provide novel potential for further drug development and treatment of RA.